Calcium Phosphate Microspheres as a Delivery Vehicle for Tooth-Bleaching Agents. (March 2018) - Mellgren, T.; Qin, T.; Öhman-Mägi, C.; Zhang, Y.; Wu, B.; Xia, W.; Engqvist, H.
Bleaching of vital teeth has become common practice in cosmetic dentistry today. Tooth sensitivity and demineralization of the enamel are, however, common side effects associated with hydrogen and carbamide peroxide bleaching. This study investigated if calcium phosphate microspheres, which have remineralizing properties, could be used as an additive without hindering the diffusion of the bleaching agent and if the spheres could be used as a carrier for carbamide peroxide. A remineralizing agent could increase the safety of bleaching and decrease the severity of its side effects. Comparisons between current hydrogen peroxide diffusion studies and previously published work are difficult since many studies include challenging-to-replicate conditions or lack reporting of important parameters. Hence, a diffusion model was designed by Wu Lab (School of Dentistry, University of California, Los Angeles) to measure the diffusion flux and determine the diffusivity of hydrogen peroxide. Physical parameters (e.g., diffusivity) could then be used for direct comparison to the results obtained by future studies. Three whitening gels with increasing amounts of spheres were formulated and tested with 2 commercially available whitening gels. The flux of hydrogen peroxide through 1-mm discs of bovine enamel was measured at steady-state conditions, and the diffusivity was calculated. The results showed that the spheres could be used as a carrier for carbamide peroxide and that the amount of spheres did not affect the diffusivity of peroxide through the enamel discs. Hence, the microspheres are considered promising as an additive to minimize side effects in bleaching gel formulation.